An adaptive Power controlled routing in Wireless Ad hoc Networks, “This paper has been withdrawn” - Ramalingam, Madhanmohan; Kannabiran, Selvakumar (Journal of Advanced Computer Science & Technology, 2012)
This paper has been withdrawn.